Sustainable Entrepreneurship: The Role of Perceived Barriers and Risk - Hoogendoorn, Brigitte (Journal of business ethics, 2019)
Entrepreneurs who start a business to serve both self-interests and collective interests by addressing unmet social and environmental needs are usually referred to as sustainable entrepreneurs. Compared with regular entrepreneurs, we argue that sustainable entrepreneurs face specific challenges when establishing their businesses owing to the discrepancy between the creation and appropriation of private value and social value. We hypothesize that when starting a business, sustainable entrepreneurs (1) feel more hampered by perceived barriers, such as the institutional environment and (2) have a different risk attitude and perception than regular entrepreneurs. We use two waves of the Flash Eurobarometer survey on entrepreneurship (2009 and 2012), which contains information on start-up motivations, start-up barriers, and risk perceptions of approximately 3000 (prospective) business owners across 33 countries. We find that sustainable entrepreneurs indeed perceive more institutional barriers in terms of a lack of financial, administrative, and informational support at business start-up than regular entrepreneurs. Further, no significant differences between sustainable and regular entrepreneurs are found in terms of their risk attitudes or perceived financial risks. However, sustainable entrepreneurs are more likely to fear personal failure than regular entrepreneurs, which is explained by their varied and complex stakeholder relations. These insights may serve as an important signal for both governments and private capital providers in enhancing the institutional climate.